新加坡华人传统社群聚落的时空演变（1819-2000）: The Spatial and Temporal Evolution of Traditional Chinese Community Settlements in Singapore (1819-2000) - Ni, William (ERUDITE: Journal of Chinese Studies and Education, 2023)
本文利用19世纪初的档案地图资料以及部分史料，以新加坡华人会馆、方言社群等地缘组织作为研究对象，从历史地理学视角梳理出新加坡从开埠时期到21世纪初，传统华人社群聚落的起源、类型特点、空间分布、时空演变的脉络；在对相关历史数据汇总分析的基础上，研究华人传统社群聚落空间变迁的驱动因素：早期新加坡多元移民社会特征与新华社会复杂的人口构成是华人传统社群聚落构建的催生力；英国殖民地政府所采取的一系列城镇规划手段是华人传统社群聚落诞生的推动力；而新加坡城市化进程则是华人传统社群聚落加快时空变迁的重要拉升力。This article uses archival map data and some historical materials from the early 19th century, and takes geographical organizations such as the Singapore Chinese Association and dialect communities as the research objects. From the perspective of historical geography, we sort out the traditional Chinese community settlements in Singapore from the opening of the port to the early 21st century. The origin, type characteristics, spatial distribution, and temporal and spatial evolution of the composition is the catalytic force for the construction of traditional Chinese community settlements; a series of town planning methods adopted by the British colonial government are the driving force for the birth of traditional Chinese community settlements; and the urbanization process in Singapore is the acceleration of time and space changes for traditional Chinese community settlements. Important lifting force.Keywords: Singapore Chinese, opening period, community，settlement，the spatial and temporal evolution